PENINGKATAN MUTU PENDIDIKAN DI MI AINUN SAHAB KABUPATEN MAJENE MELALUI KEPEMIMPINAN KEPALA MADRASAH - Asliah, Asliah; Farida, Farida (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2023)
Leadership is needed in a madrasa, especially the leadership of the head of the madrasa. Madrasah leadership is also needed for the quality of education. Improving the quality of education is needed to improve the quality of madrasas. Research objectives: 1. To describe the leadership of the principal at MI Ainun Sahab, Majene Regency. 2. Describe the quality of the teaching staff at MI Ainun Sahab, Majene Regency. This study uses a qualitative method with a qualitative descriptive design, data collection techniques used are observation, interviews, and documentation with data analysis using Data Reduction, Data Display, and Conclusion Drawing. The results of the study: 1. The leadership of the principal at MI Ainun Sahab, Majene Regency is quite good. He is in charge of institutions at MI Ainun Sahab, Majene Regency. Here the style used by the head of the madrasa to lead is to use a democratic style, where the head of the madrasa always draws closer to teachers, students and madrasa employees with the aim of guiding or protecting the teacher in carrying out his duties and obligations. 2. The principal is a person who plays an important role in the quality or quality of the madrasa itself. Therefore, leadership from the head of the madrasah is needed to improve the quality of teaching staff. The performance of the teaching staff can be seen from the performance of the teaching staff as something that is achieved, the achievements shown, the ability to use resources to achieve goals in education effectively and efficiently. This was carried out at MI Ainun Sahab, Majene Regency, where the head of the madrasa placed teaching staff according to the abilities of the educators because it was seen from a professionalism perspective.